Application of Household PHBS Education in Improving Family Self-Care in Sub-districts Medan Tuntungan - Siska Mariany Ocfica Napitupulu; Reny Juliana Sihombing; Julaiha Siregar (Cattleya Darmaya Fortuna, 2025)
Clean and Healthy Living Behaviors (PHBS) are a set of behaviors that are practiced on the basis of learning that enable a person or family to help themselves in the health field and play an active role in realizing public health. Based on an initial survey conducted by researchers in Mangga Village about the implementation of clean and healthy living behaviors, many families have not implemented it. This is evidenced by the fact that there are still people who suffer from diarrhea and dengue disease. This type of research is descriptive in nature which aims to describe the Overview of the Implementation of Clean and Healthy Living Behaviors in the Household Order. The sample in this study is one of the core families, which is 36 people, which were taken using a random sampling system. The data used is primary data, namely data collected using questionnaires obtained from respondents. The results of the implementation of clean and healthy living behaviors regarding the availability of clean water were good, as many as 21 people (58.3%), about washing hands were good, as many as 20 people (55.6%), about the availability of healthy latrines were good, as many as 23 people (63.9%), about eradicating mosquito larvae were sufficient, as many as 17 people (47.2%), about eating fruits and vegetables every day was enough, as many as 23 people (63.9%), about doing physical activity every day is enough, as many as 20 people (55.6%), about not smoking indoors is less, as many as 17 people (47.2%). The implementation of Clean and Healthy Living Behaviors in the Household Order in Mangga Village in 2025 is sufficient, as many as 23 people (63.9%). It is hoped that families can implement clean and healthy living behaviors in daily life, so that families do not get sick easily. It is hoped that the community/environment will be able to create a healthy environment to support the creation of healthy villages and for health workers to continue to provide health information through counseling on clean and healthy living behaviors in the household order.